Rancang Bangun Aplikasi Pendeteksi Golongan Darah Dan Rhesus Berbasis Internet Of Things - Gunawan, Indra; Fathurrahman, Imam; Wasil, Muhammad; Jumawal (Fakultas Teknik Universitas Hamzanwadi, 2024)
The rapid advancement of technology in today's world has led to significant progress in various aspects of human life, including healthcare. Nowadays, numerous advanced medical devices are being created to facilitate healthcare services. Health is a crucial element in human life, which is why regular monitoring through laboratory tests is essential. Blood type and Rh factor are critical pieces of information in the medical field, especially for blood transfusions and specific medical treatments. However, determining a person's blood type still relies on manual methods, requiring experienced professionals and a considerable amount of time to analyze blood samples. To address this challenge, an Internet of Things (IoT)-based blood type and Rh factor detection device is being developed.The main objective of this research is to design and implement an efficient, fast, and user-friendly device for detecting blood type and Rh factor using IoT technology. Furthermore, this device aims to simplify data storage after conducting a large number of blood type checks, eliminating the need for repeated testing. The creation of this blood type and Rh factor detection device requires several components, including the WiFi module ESP8266, Arduino Uno, and a light sensor built with LDR components. The results will be displayed on a 16x2 LCD and the data obtained from the testing process will be sent to a designated web page. This data will be stored in a MySQL database and subsequently presented on a website.